Methodology of Assessment of Athletes' Jumping Skills Using Electronic Equipment - Soyib Tajibaev; Shukhratulla Allamuratov; Bekir Erhan; Turabjon Ismoilov; Khabibulla Tursunov; Farrukh Kuchkarov (Слобожанський науково-спортивний вісник)
Background and Study. Vertical jump performance is a critical factor in volleyball, significantly influencing actions like spiking, blocking, and serving. Accurate assessment of jump height is essential for optimizing training strategies, especially at the elite level.